Strategi Pemasaran Produk Gadai Emas (RAHN) Pada Bank BJB Syariah KCP Tambun - Ade Djuanda (Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this research is to find out more about the marketing strategy that is most suitable for Sharia Gold Pawn Products at Bank BJB Sharia KCP Tambun in order to spur growth and development in business competition. This study uses a qualitative approach with data collection techniques in the form of documentation, interviews and observations. The results of the study show that the marketing strategies implemented by the Sharia Gold Pawn Products at Bank BJB Sharia KCP Tambun include; promotion strategy, price strategy, product strategy and distribution strategy.